2018
DOI: 10.1002/marc.201800431
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Semi‐Fluorinated Alkyl Side Chains on Conjugated Polymers with Planar Backbone in Organic Field‐Effect Transistors

Abstract: Newly synthesized donor-acceptor (D-A) type of conjugated copolymer (PCTV-BTzF) with semi-fluorinated alkyl side chains, which has good solubility in common organic solvents, is described. Unlike polymers with hydrocarbon-based alkyl side chains, semi-fluorocabonated polymer leads to intriguing results. First, the self-organization behavior of the semi-fluoroalkyl side chains by the self-aggregate propensity between hydrocarbon and fluorocarbon induces patterned microstructural morphology in polymer films; sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Driven by the advantage of processing conjugated materials from solution, a simple and productive organizing principle has emerged that separates structures into two domainsthe “main chain” contains all the atoms with electrons that participate in the π-conjugated system, while pendant “side chains” are not electronically coupled to the main chain. Side chains are usually long, branched alkyl groups that impart solubility in organic solvents, although hydrophilic chains and fluorinated chains are also used. Although numerous efforts have focused on engineering discrete noncovalent interactions within and between main chains, , this conceptual orthogonality has led to side chains being largely ignored in rational design. The most common efforts of “side-chain engineering” aim to minimize their impact on conformation and packing of main chains.…”
Section: Introductionmentioning
confidence: 99%
“…Driven by the advantage of processing conjugated materials from solution, a simple and productive organizing principle has emerged that separates structures into two domainsthe “main chain” contains all the atoms with electrons that participate in the π-conjugated system, while pendant “side chains” are not electronically coupled to the main chain. Side chains are usually long, branched alkyl groups that impart solubility in organic solvents, although hydrophilic chains and fluorinated chains are also used. Although numerous efforts have focused on engineering discrete noncovalent interactions within and between main chains, , this conceptual orthogonality has led to side chains being largely ignored in rational design. The most common efforts of “side-chain engineering” aim to minimize their impact on conformation and packing of main chains.…”
Section: Introductionmentioning
confidence: 99%
“…With the progress in research, it has been realized that side chains can do more to modulate the solid-state construction and microstructure of polymers. Therefore, various side chains have been designed to study their effects on polymers and their devices. The steric hindrance effect of branched alkyl chains caused by their huge size and insulation characteristics is considered to be unfavorable to charge transmission . It is found that this negative effect will be reduced as the branching position is properly far away from the conjugated main chains.…”
Section: Introductionmentioning
confidence: 99%
“…Solution-processable organic semiconductors (OSCs) are composed, in most cases, of p-electron cores bonded with functional substituents. [1][2][3][4][5] The substituents are structurally exible and electrically inert, as observed in typical substituents such as normal and branched alkyl chains, [6][7][8][9][10][11][12][13][14][15] silylethynyl, [16][17][18][19] uoroalkyl, [20][21][22][23][24] or others, [25][26][27][28][29] which is in contrast to the rigid nature of p-electron cores that play major roles in the carrier transport characteristics. However, the role of the substituents is oen critical, not only for increasing the solubility characteristics, but also for affecting the whole material characteristics through the variation of intermolecular packing geometries.…”
Section: Introductionmentioning
confidence: 99%